How charitable giving affects litigation duration? Empirical evidence from China. - Feng Zhu (PLoS ONE)
Charitable donations are an important manifestation of corporate social responsibility. Current research focuses on the economic effects of corporate donations while ignoring their legal effects in the litigation field. This paper utilizes litigation and arbitration data from A-share listed companies in Shanghai and Shenzhen from 2008 to 2021 to investigate the impact and mechanism of charitable donations on the litigation duration of listed companies. The study finds that: (1) Charitable donation behavior can significantly shorten the litigation duration of listed companies. (2) This effect is particularly significant when listed companies are plaintiffs, but not significant when they are defendants. (3) The negative relationship between charitable donations of listed companies and litigation duration is achieved through reputation mechanisms. (4) This effect is more significant for listed companies located in the Northeast region and regions with a lower degree of marketization when facing civil and arbitration cases. (5) Additionally, by constructing panel data on whether companies are involved in litigation and as defendants, it is shown that corporate charitable donations not only have the function of "compensating" reputation but also serve as a kind of "insurance" for reputation. After robustness tests and overcoming endogeneity issues, the above conclusions still hold. This paper clarifies the implicit interaction mechanism between listed companies and judicial departments, enriches research in the field of organizational reputation theory, and is of significant importance for deeply understanding the motivation of corporate charitable donations.